The effect of sintering temperature on Cu-CNTs nano composites properties produced by PM method - Darabi Marjan; Rajabi Masoud; Junipour Behzad; Noghani Mohammad Talafi (Science of Sintering, 2018)
In this research work, copper and CNTs have been processed using high energy milling in different milling times (5, 10 and 15 hours). FESEM and XRD have been used to characterize the milled powders. The FESEM micrographs of the milled powders indicated that the morphology of powders changed from spherical shape to flake as milling time increased. The effect of sintering temperature as well as CNTs content on the properties of Cu-CNTs nanocomposite has been investigated. The optimum sintering temperature to produce Cu-CNTs nanocomposites is determined to be 900 oC. The microstructure and phase analysis of Cu-CNTs nanocomposites were studied by field emission scanning electron microscopy and X-ray diffraction. Mechanical properties of nanocomposite samples at various sintering temperatures were investigated. Cu-CNTs nanocomposite with 4 vol.% CNTs fabricated by powder metallurgy method indicated the highest value of the micro-hardness and bending strength as compared to pure copper.